Analysis of the tourist offer of the Pueblos mágicos Ecuador - 4 mundos program - Molina Velásquez, Edison Rubén (2021)
In 2018, the Ministry of Tourism of Ecuador (MINTUR) signed an agreement with the Secretariat of Tourism of Mexico (SECTUR) for the implementation and development of the Pueblos Mágicos Ecuador - 4 Mundos Development Program. After three years of operation and taking into account the impact of the COVID-19 pandemic, the objective of this work is to analyze the tourist offer and promotion to determine the current status of the implementation of the Magic Towns Ecuador program. The research is descriptive and comparative; of mixed methodological approach; the study is complemented with the use of geographic information systems GIS, to represent the territorial distribution and the concentration of service providers. The main results reflect the typology of tourist attractions, classification and concentration of service providers, certifications and names, classification of conservation areas and information regarding tourism promotion through digital platforms. Pueblos Mágicos is a management model that promotes tourist activity, rescuing the local identity and the revaluation of heritage. It depends directly on the commitment of the actors linked to the program to establish promotional strategies.